Mathematical Model of Dengue Transmission Dynamics with Adaptive Human Behavior - Dayap, Jonecis A.; Rabajante, Jomar F. (The Indonesian Bio-Mathematical Society, 2025)
Dengue fever, a viral disease spread by Aedes mosquitoes, is a significant public health issue in tropical and subtropical regions. Behavioral adaptations in response to perceived infection risks can significantly reduce disease incidence and prevalence through the adoption of control measures. However, most existing models developed to assess the mitigation of dengue only implicitly account for this adaptive behavior within the dynamics of disease transmission. In this paper, we propose a mathematical model that explicitly incorporates adaptive human behavior in response to community infection levels into the transmission dynamics of dengue and investigates how this behavior affects transmission. Analytical results of the model reveal that the diseasefree equlibrium is locally asymptotically stable when the basic reproduction number (R0) is less than 1. The model parameters are calibrated using daily dengue case data from the 2015 outbreak in Kaohsiung City, Taiwan, resulting in a calculated basic reproduction number (R0) of 1.42. Sensitivity analysis indicates that to reduce the reproduction number, efforts should focus on reducing mosquito-human contact, controllingthe mosquito population, and improving hospital treatment. Numerical simulations demonstrate that positive behavioral changes in response to increasing infection levels significantly reduce dengue cases when selfprotectiveand vector control measures are effectively implemented. Our results emphasize the importance of enhancing these behavioral changes to achieve a substantial reduction in dengue incidence. This highlights the critical role of reporting disease prevalence, educating individuals on effective dengue mitigation strategies, and ensuring access to resources necessary for high-efficacy self-protection and vector control measures. By promoting awareness and providing support for control measures such as mosquito repellents, bed nets, insecticide-treated curtains, and community clean-up drives to eliminate mosquito breeding sites, governments can significantly enhance the effectiveness of dengue control programs.